2007
DOI: 10.1099/mic.0.2007/007856-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from xylose by recombinant Saccharomyces cerevisiae expressing protein-engineered NADH-preferring xylose reductase from Pichia stipitis

Abstract: A recombinant Saccharomyces cerevisiae strain transformed with xylose reductase (XR) and xylitol dehydrogenase (XDH) genes from Pichia stipitis (PsXR and PsXDH, respectively) has the ability to convert xylose to ethanol together with the unfavourable excretion of xylitol, which may be due to intercellular redox imbalance caused by the different coenzyme specificity between NADPH-preferring XR and NAD + -dependent XDH. In this study, we focused on the effect(s) of mutated NADH-preferring PsXR in fermentation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 39 publications
4
125
0
4
Order By: Relevance
“…Comparison the obtained partial amino acid sequences of C. tropicalis A26 to those of other yeast strains in Gene Bank database revealed that C. tropicalis A26 xylose reductase possessed 98.4%, 78.5%, and 77.5% identity and 99.0%, 86.4%, and 85.9% similarity to xylose reductase of CtrXR of C. tropicalis (ABX60132C), CtXR of C. tenuis (AAC25601), and CsXR of C. shehatae (ABK35120), respectively (Table 4). Amino acid sequence alignment of the partial xylose reductase revealed tetra amino acid motif (Ile-Pro-Lys-Ser), an NAD(P)H species motif 14,17,53 ( Fig. 2).…”
Section: Cloning Of C Tropicalis A26 Xylose Reductase Genementioning
confidence: 99%
See 3 more Smart Citations
“…Comparison the obtained partial amino acid sequences of C. tropicalis A26 to those of other yeast strains in Gene Bank database revealed that C. tropicalis A26 xylose reductase possessed 98.4%, 78.5%, and 77.5% identity and 99.0%, 86.4%, and 85.9% similarity to xylose reductase of CtrXR of C. tropicalis (ABX60132C), CtXR of C. tenuis (AAC25601), and CsXR of C. shehatae (ABK35120), respectively (Table 4). Amino acid sequence alignment of the partial xylose reductase revealed tetra amino acid motif (Ile-Pro-Lys-Ser), an NAD(P)H species motif 14,17,53 ( Fig. 2).…”
Section: Cloning Of C Tropicalis A26 Xylose Reductase Genementioning
confidence: 99%
“…Cocultivating of S. cerevisiae and S. stipitis strains to co-ferment glucose and xylose remains unsatisfactory, due to their difference in fermenting condition and ethanol tolerance 12,13 . S. stipitis strain prefers to ferment glucose more than xylose while it has lower ethanol tolerance than S. cerevisiae strain 14 . So xylose was not fermented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expressing the XI pathway can avoid the cofactor imbalance problem under anaerobic conditions, but xylitol accumulation has also been observed in strains expressing XI (17,18,20), because the nonspecific aldose reductase encoded by the GRE3 gene can produce xylitol from xylose (27). Various rational approaches have been used to reduce xylitol accumulation and improve xylose utilization, such as optimizing the expression levels of xylose-assimilating reactions (26), engineering the cofactor preference of XR/XDH enzymes (28)(29)(30)(31)(32)(33), perturbing the pentose phosphate pathway by gene knockout or overexpression (34)(35)(36)(37)(38)(39), or deleting GRE3 in strains expressing the XI pathway (21,40,41). While extensive previous efforts focused on manipulating intracellular metabolic reactions to improve xylose utilization and reduce by-product (e.g., xylitol) accumulation, controlling the xylitol export process might also be a meaningful strategy for reducing its formation and increasing carbon flux toward target products.…”
mentioning
confidence: 99%